2016
DOI: 10.1186/s12970-016-0157-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of caffeine ingestion on strength and power performance in female team-sport players

Abstract: BackgroundThe aim of this study was to examine the influence of caffeine supplementation on knee flexor and knee extensor strength before, during and after intermittent running exercise in female team-sport players taking oral contraceptive steroids (OCS).MethodTen healthy females (24 ± 4 years; 59.7 ± 3.5 kg; undertaking 2–6 training sessions per week) taking low-dose monophasic oral contraceptives of the same hormonal composition took part in a randomised, double-blind, placebo-controlled crossover-design tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
3
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 36 publications
1
45
3
6
Order By: Relevance
“…The effect of caffeine on maximal isometric strength observed in this study is in agreement with Warren et al's meta-analysis findings, 6 who found caffeine to have a moderate effect on isometric knee extensor strength. On the other hand, Ali et al 14 found no effects of 6 mg•kg −1 caffeine on knee extensor isometric strength in women. However, their protocol measured maximal muscle strength between fatiguing blocks of sprints and consequently, might have masked a caffeine-induced effect on maximal strength.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The effect of caffeine on maximal isometric strength observed in this study is in agreement with Warren et al's meta-analysis findings, 6 who found caffeine to have a moderate effect on isometric knee extensor strength. On the other hand, Ali et al 14 found no effects of 6 mg•kg −1 caffeine on knee extensor isometric strength in women. However, their protocol measured maximal muscle strength between fatiguing blocks of sprints and consequently, might have masked a caffeine-induced effect on maximal strength.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, variations in strength and power have been demonstrated throughout the menstrual cycle, 13 which can cause noise in performance data and affect overall results. Taken together, although there are a number of studies demonstrating that caffeine clearly has an ergogenic effect in females, 9,[14][15][16] the information about the effect of caffeine on muscle performance in women is uncertain, especially in strength and power performance. As an example, a recent meta-subgroup analysis examined the effects of caffeine on muscle power in females for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, CAF failed to increase CMJ and SJ performance, corroborating previous studies showing no improvement in CMJ after CAF intake in male adult soccer players 32 and in female team-sport players. 33 Other studies, however, have reported an ergogenic effect of CAF on jump performance in male adolescent basketball players 34 (ES = 0.181) and male adult volleyball players 12 (ES = 0.399). It is difficult to explain the reason for these contradictory findings, but an improvement in jump performance with CAF ingestion, when present, would be associated with a better neuromuscular function, mainly due to the higher conduction speed and/or the greater recruitment of muscle fibers.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, the effects of caffeine supplementation were evaluated in men and may not be generalizable to women CrossFit ® participants. Caffeine supplementation in women is complicated by the effects of estrogen and oral contraceptive steroids on caffeine metabolism, both of which appear to prolong the effects of caffeine in the body [5,51]. To increase internal validity, participants performed the workout alone, with no clock visible, and no music was playing.…”
Section: Discussionmentioning
confidence: 99%